Synthesis of Bullvalenes: Classical Approaches and Recent Developments - Ferrer, Sofia; Echavarren, Antonio M. (Synthesis, 2019)
The goal of this short review is to provide an overview of the different synthetic methodologies applied along the years for the synthesis of bullvalenes, prototypical fluxional molecules that were key in the understanding of valence tautomerism phenomena. Some interesting applications of these unique shapeshifting compounds are also presented.1 Introduction2 Classical Syntheses of Bullvalenes3 Recent Developments in the Synthesis of Bullvalenes4 Applications of Bullvalenes5 Conclusion
Keywords: bullvalenes; fluxional; cage-like molecules; shapeshifting; degenerate isomers